Escola e Memória - Oliveira, Karla Roberta Brandão de (2021)
As unfinished beings (FREIRE, 2003), we assume that we are in a constant process of formation and that it happens in different spaces and times. However, it is at school that we experience distinct learning experiences, out of a formal education grounded and organized for specific purposes of society. Based on the assumption that the school is a place of memory, we argue that the history of individuals helps us understand social conditions and the history of the community. That said, the research carried out revolved around an experience of teacher training in particular – the PARFOR/URCA pedagogy course. We were interested in understanding the meanings that student-teachers attributed to it. The guiding questions of the research were: to what extent did the training experiences provided by the Pedagogy/PARFOR/URCA course, in the set of relationships experienced, favored transformations in the ways of acting and perceiving the world by the student-teachers? What is the perception they had about the influence of this training on the knowledge, feelings and actions of their teaching practice? What experiences have been most significant for changing their understanding of the world and their relationships? To what extent did the experiences from the training received influenced their teaching action and understanding of pedagogical issues? The objectives defined for the study accounted for a knowledge to be known from the memorialistic records of the PARFOR/URCA students-educators, who are also subjects of this investigation. The preferred methodological approach in this thesis was that of life history. This option is consistent with the intention to work with the autobiography. In this research we tried to accept the narratives of student-teachers without judgments, even though we are aware that events did not always happen in the way they are reported, considering that remembering is always updating and reframing images and feelings. At the end of the investigation, we found that the history of the student-teachers mixes with the history of the rural school and reveals traces of it, such as the precarious financial conditions and the presence of illiteracy in their family nucleus. Also noteworthy were the efforts of mothers, fathers, grandparents and grandfathers to have their daughters study; the reality of the schools, where they studied and today teach, marked by: inadequate physical structure, absence of didactic material, multiseriate organization of classrooms, unqualified teachers and the difficulty of moving from home to school, due to the terrible conditions of the school and road transport. We conclude that the Pedagogy/PARFOR course is an important milestone in the lives of memorialists. The life history of these women indicates that, without the initiative of bringing higher education to small municipalities in the interior of the state of Ceará, they would hardly have achieved the long-awaited graduation that, in addition to a personal dream, is essential for the change of the quality of education that we have offered to children and adolescents in these locations.